PENGARUH WORD OF MOUTH, KUALITAS LAYANAN, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS TF MIRACLE WATER) - asmayaty, indah (Jurnal Magister Manajemen, 2017)
This research main aimed was to analys the effect of word of mouth (WOM), service quality, product quality, and promotion on the consumers purchasing decision. The research was conducted by the consumers of TF Miracle Water. This research was done based on survey received from 100 respondent. Based on the consumer surveys many find that WOM, service quality, and promotion have positive impact on purchasing decision. While product quality had positive but not significant effect on the consumers purchasing decision. This research showed that WOM is the main importance on consumer purchased. Research shows TF Miracle Water pay attention and consider the WOM, service quality, product quality, and promotion more comprehensively to determine the marketing strategy to build consumers purchasing decision. Keywords : Word Of Mouth (WOM), Service Quality, Product Quality, Promotion, and Purchasing Decision.